Marginal filling and adhesive resistance of bulk fill resin applying 18% edta gel compared with 37% phosphoric acid gel in vitro dental conditioning. - César Cayo; Lorena Llancari; Román Mendoza; Luis Cervantes (Universidad de Concepción., 2019)
Objective. To evaluate the degree of marginal sealing and adhesive strength in Bulk-Fill resin by applying 18% EDTA gel compared to 37% phosphoric acid gel in dental conditioning. Materials and methods. The study was transversal, experimental comparative, and applied. The sample group consisted of 60 teeth with Class I cavities, which were later subjected to conditioning. This was carried out separately with phosphoric acid gel for 15 seconds, and 18% EDTA gel within two different time frames: 60 and 90 seconds. All samples were incubated at 37ºC for a period of 24 hours and thermocycled between 5 to 55ºC for 500 cycles. To assess microfiltration, they were immersed in methylene blue at 37ºC for 4 hours, and were later sectioned and observed through a stereomicroscope. In order to perform the traction, the conventional testing machine was used at a speed of 0.75mm/min until the screw with the resin detached. Results: Samples conditioned with 37% phosphoric acid showed a greater degree 1 microfiltration and a mean adhesive resistance of 7.97 MPa. The same number of microfiltration grades 1 and 2 was found when using EDTA gel for 60 seconds, with a mean tensile strength of 8.8 MPa. On the other hand, applying EDTA gel for 90 seconds showed mostly grade 1 microfiltrations, and to a lesser extent, grade 0 and 2, with a mean resistance of 9.2 MPa. Conclusion: There are no statistically significant differences regarding adhesive strength between the two gels; however, better marginal filling was observed when samples were conditioned with 18% EDTA gel for 90 seconds.